2020
DOI: 10.1002/solr.202000610
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Surface N‐Vacancy Defects of Ultrathin Mesoporous Carbon Nitride Nanosheets as Efficient Visible‐Light‐Driven Photocatalysts

Abstract: Graphitic carbon nitride (GCN) has become an attractive photocatalyst for solar energy conversion, but the photocatalytic activity of GCN is still limited by the extremely fast electron–hole recombination. Herein, a defective ultrathin mesoporous graphitic carbon nitride (DUMCN) photocatalyst with high specific surface area and mesoporous structure is fabricated through a facile three‐step heat‐treatment strategy, which reduces the distance of bulk photogenerated carriers to the surface, resulting in efficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 62 publications
(77 reference statements)
0
16
0
Order By: Relevance
“…[21,22] Moreover, H 2 O adsorption and activation on surface active sites of photocatalysts are also important for STH process. [23][24][25][26][27] In S-scheme photocatalytic system, Fermi energy level difference ensures that the so-generated built-in electric field promotes the efficient separation and migration of photogenerated electrons and holes through the curved and matched energy bands. The spontaneous electron migration induced by Fermi energy difference can activate the surface of photocatalytic materials, provide the adsorption and activation of H 2 O molecules, and decrease the reduction overpotential of H 2 O.…”
Section: H 2 O Splitting Into H 2 Fuelmentioning
confidence: 99%
“…[21,22] Moreover, H 2 O adsorption and activation on surface active sites of photocatalysts are also important for STH process. [23][24][25][26][27] In S-scheme photocatalytic system, Fermi energy level difference ensures that the so-generated built-in electric field promotes the efficient separation and migration of photogenerated electrons and holes through the curved and matched energy bands. The spontaneous electron migration induced by Fermi energy difference can activate the surface of photocatalytic materials, provide the adsorption and activation of H 2 O molecules, and decrease the reduction overpotential of H 2 O.…”
Section: H 2 O Splitting Into H 2 Fuelmentioning
confidence: 99%
“…3f exhibits the N 2 adsorption–desorption isotherms of the ZIS and Al-ZIS nanosheets, and both samples show typical type-IV isotherms according to the IUPAC classification and a hysteresis loop at a relative pressure ( p / p 0 ) from 0.4 to 1.0, indicating that there are numerous mesoporous structures in the ZIS and Al-ZIS nanosheets. 33–35 Based on isotherms, Brunauer–Emmett–Teller (BET) surface areas and pore volumes were further obtained. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It can be seen that HAp/g-C 3 N 4 illustrated a higher amount of OHc radical in comparison with HAp and g-C 3 N 4 . 25,26 ESR analysis also conrmed the production of more OHc radicals by HAp/g-C 3 N 4 . Other works have also shown that the g-C 3 N 4 nanocomposite produced more oxygen radicals under light irradiation in comparison to single g-C 3 N 4 .…”
Section: Photocatalytic Evolution Of Hap/g-c 3 N 4 Nanocompositementioning
confidence: 93%
“…23 An effective photocatalyst of oxygen edged holey g-C 3 N 4 nanosheets was constructed under photo-Fenton-reaction and UV irradiation with remarkable pollutant degradation. 24,25 Moreover, porous holey nanosheets were synthesized via the pre-polymerization method showing high photocatalytic H 2 evolution under ammonia gas pressure. 26 Also, similar works for the preparation of the mentioned morphologies suffer from complex processes and are timeconsuming.…”
Section: Introductionmentioning
confidence: 99%